Morphological characteristics and determination of volatile organic compounds of Diospyros virginiana L. genotypes fruits - Grygorieva, Olga; Klymenko, Svitlana; Vergun, Olena; Hudz, Nataliia; Nikolaieva, Nataliia; Schubertová, Zuzana; Palamarchuk, Olena; Brindza, Ján (Potravinarstvo Slovak Journal of Food Sciences, 2017)
The aim of this study was to determine morphometric differences of fruits and seeds between 19 selected American persimmon (Diospyros virginiana L.) genotypes. The genotypes of American persimmon have been growing more than 15 years in Forest-Steppe of Ukraine in the M.M. Gryshko National Botanical Garden of NAS of Ukraine. They are well adapted to the climatic and soil conditions. The fruits were collected at the period of their full maturity (October). The population differs in a weight, shape, size and color of fruits and seeds. Their morphometric parameters were following: fruit weight from 2.30 to 81.30 g, fruit length from 8.84 to 49.73 mm, fruit width from 12.84 to 55.34 mm, seed weight from 0.1 to 1.0 g, seed length from 8.30 to 20.88 mm, fruit width from 7.04 to 14.88 mm, seed thickness from 1.98 to 7.09 mm and number of seeds in the fruit from 1 to 8. Partenocarpic fruits are found in some genotypes. The shape indexes of fruits and seeds were found ranging from 0.74 to 1.10 and from 1.01 to 1.77, respectively. During the analysis of qualitative composition and quantitative content of volatiles of fruits from the 4 perspective genotypes of Diospyros virginiana 106 compounds were detected. From them 83 compounds were identified. The identified compounds belong to alcohols, saturated and unsaturated aldehydes, ketons, fatty acids, esters, terpenoids etc. The fruits are rich in fat acids. The outcome of the research points to the fact that the genepool of Ukrainian Diospyros virginiana is a rich source of genetic diversity and might be used in selection for creation a new genotypes and cultivars. <!–[endif] –>